2002
DOI: 10.1021/ma020226h
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Telechelics Incorporating Polyhedral Oligosilsesquioxane:  1. Synthesis and Characterization

Abstract: Well-defined amphiphilic telechelics incorporating polyhedral oligosilsesquioxane (POSS) were synthesized by direct urethane linkage between the diol end groups of poly(ethylene glycol) (PEG) homopolymers and the monoisocyanate group of POSS macromers. The hydrophobicity of the amphiphilic telechelics was varied by using a series of PEG homopolymers of increasing molecular weight, resulting in control over molecular architecture by hydrophilic/hydrophobic balance. The synthesized amphiphilic telechelics were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
146
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(158 citation statements)
references
References 36 publications
9
146
1
2
Order By: Relevance
“…Furthermore, there is also a slope change around Π ≈ 30 mN m -1 leading to film heterogeneity as seen by BAM (Figure 4). [37][38][39] R is a cyclohexyl group for these studies. with an attendant shift of A 0 ≈ 1.4 nm 2 POSS -1 .…”
Section: Compression Isotherm Studies Of Peg Vs Poss-peg-possmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there is also a slope change around Π ≈ 30 mN m -1 leading to film heterogeneity as seen by BAM (Figure 4). [37][38][39] R is a cyclohexyl group for these studies. with an attendant shift of A 0 ≈ 1.4 nm 2 POSS -1 .…”
Section: Compression Isotherm Studies Of Peg Vs Poss-peg-possmentioning
confidence: 99%
“…40 POSS-PEG-POSS samples were synthesized by direct urethane linkages between the hydroxyl end groups of PEG homopolymers and the monoisocyanate group of POSS macromers (isocyanatopropyldimethylsilylcyclohexyl-POSS) provided by the Air Force Research Laboratories, AFRL/PRSM. 37,38 The telechelic polymers are designated here as POSS-PEG 1K -POSS, POSS-PEG 2K -POSS, POSS-PEG 3.4K -POSS, POSS-PEG 8K -POSS, and POSS-PEG 10K -POSS, and their properties are summarized in Table 1. In addition, a high molar mass PEO sample (M n ) 90 kg mol -1 , polydispersity index of M w /M n ) 1.09) was purchased from Polymer Source, Inc., and was used as received.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 10"wt% the hybrids turned out to be homogeneous, whereas the sample blend containing 20"wt% of POSS-OH (TPU/POSS-OH (20)) clearly showed two separated phases at the micron scale. In the case of the sample based on isobutyl-POSS, (TPU/oib-POSS(10)), a solvent capable to swell the polymer and completely solubilize POSS molecules was found to extract the POSS entirely, evidencing the efficiency of the experimental procedure for the extraction of unbound silsesquioxanes.…”
Section: Study Of Hybrid Systems Characteristicsmentioning
confidence: 99%
“…POSS hybrids based on polyurethane (PU) have been previously prepared by in situ polymerization. Indeed, synthesis of amphiphilic telechelic oligourethanes with terminal POSS groups through reaction of monoisocyanate substituted POSS and oligo (oxyethylene diol) and investigation of the structure of such polymers in solution were reported [20,21]. Interestingly, chemical reaction of monoisocyanate substituted POSS fragments with polyamidoamine of a dendritic nature (polyamidoamine PAMAM dendrimers) leads to the formation of several organoinorganic core-shell type nano-hybrids [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has nanometer-size cubic structure with wide surface area and controlled porosity, and can be functionalized with a wide variety of organic groups as monomer in a typical polymerization. Use of POSS derivatives as monomer has been demonstrated to be an efficient method in the design of nanocomposite materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] as well as in designing various hybrid polymers with POSS as side groups [16][17][18][19][20][21][22][23][24][25][26][27][28] or as chain end, [29][30][31] which exhibit desirable unique properties. Laine et al reported the synthesis of multi-functinal POSS as precursors of nanocomposite materials from commercially available typical silane-functionalized cubic silsesquioxane, octakis(dimethylsiloxy)octasilsesquioxane (Q 8 M 8 H ) by hydrosilylation.…”
mentioning
confidence: 99%